A Study of the Complete Response Rate with a Combination of High Dose Cytarabine and Cladribine in Refractory and Relapsed Acute Leukemia - Reza Safaei Nodehi; Behrouz Gharib; Ramazaali Sharifian; Amirhossein Emami; Majid Moghadaszadeh; Sara Sardashti (International Journal of Hematology-Oncology and Stem Cell Research, 2010)
Introduction: Acute leukemia covers a broad spectrum of hematological clonal diseases originating from the malignant transformation of stem cells. Current chemotherapeutic methods result in an incomplete response to primary regimens in 30-40% of cases. Methods: 20 patients who had been diagnosed with acute leukemia and who had displayed defined criteria in order to enter our study, were assessed in a clinical trial. A combined chemotherapy regimen with Cladribine and Cytarabine was used in the evaluation of the response to treatment and other parameters between the two ALL (acute lymphoblastic leukemia) and AML (acute myeloid leukemia) groups. Results: Average patient age was 32.5±11.3. 13 patients (65%) were male and 7 patients (35%) were female. The average blast count was 67.7% ±18.3% in the AML group while this count was 63.8±19.6% in the ALL group. 5 out of 11 (45.5%) AML patients and 4 out of 9 ALL patients (44.4%) died during our experiment with no significant statistical difference between the two groups (P=0.65). 4 of the AML patients (36.4%) showed complete response while 4 cases (36.4%) were refractory. In the ALL group, there were 3 patients (33.3%) with complete response and 5 (55.6%) were refractory cases. Conclusion: According to the results of the present study compared to other similar studies, a combined chemotherapy regimen of Cladribine and Cytarabine can be used in acute relapsed and refractory leukemia, however, with high toxicity and high early mortality. If factors are controlled, mortality can be reduced in some cases.